Faktor-Faktor yang Mempengaruhi Keputusan Pengunjung XXI di Ramayana Ciplaz Kota Bandar Lampung - Amanda, Oktavina; Astuti, Sri Yuli (STIES ALIFA, 2024)
ABSTRACT XXI Cinema is a place to watch movies by offering the best facilities for its visitors. Having been in the entertainment industry for more than 30 years, XXI is committed to always maintaining the quality it has. XXI is a new form of Cinema 21. Visitors' decisions in visiting XXI Cinema at Ramayana Ciplaz Plaza cannot be separated from the role of marketing management they have. Until now, XXI is still the choice for customers who like to watch movies. The research method used is quantitative causal. The number of samples obtained through a questionnaire was 61 respondents, with the data processing technique being multiple linear regression. The results of the study stated that location has a positive effect on visitor decisions, the more comfortable and strategic the location, the more customers will decide to visit XXI. Ticket prices have a positive effect on visitor decisions, the cheaper the cinema tickets, the more individuals will decide to visit XXI. Attractions have a positive effect on visitor decisions, the more cinema attractions in presenting the latest films, the more individuals will visit XXI.